Turned away : the treatment of single homeless people by local authority homelessness services in England /: the treatment of single homeless people by local authority homelessness services in England. (October 2014) - Dobie, Sarah; (Charity worker), Sanders, Ben; Teixeira, Lígia; Crisis (Organization),
No abstract available